2015
DOI: 10.1098/rsta.2014.0398
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput system for high-quality tomographic reconstruction of large datasets at Diamond Light Source

Abstract: Tomographic datasets collected at synchrotrons are becoming very large and complex, and, therefore, need to be managed efficiently. Raw images may have high pixel counts, and each pixel can be multidimensional and associated with additional data such as those derived from spectroscopy. In time-resolved studies, hundreds of tomographic datasets can be collected in sequence, yielding terabytes of data. Users of tomographic beamlines are drawn from various scientific disciplines, and many are keen to use tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 18 publications
0
82
0
Order By: Relevance
“…Samples were rotated from 0 to 180 • at a step of size of 0.05 • collecting in total 3,601 projections at 40 ms exposure. Projections were then reconstructed into 3D dataset using filtered back projection algorithm (Atwood et al, 2015). Obtained µCT data were then analyzed using Fiji R (Schindelin et al, 2012).…”
Section: Micro-computed Tomographic (µCt) Studies Of Materials Structuresmentioning
confidence: 99%
“…Samples were rotated from 0 to 180 • at a step of size of 0.05 • collecting in total 3,601 projections at 40 ms exposure. Projections were then reconstructed into 3D dataset using filtered back projection algorithm (Atwood et al, 2015). Obtained µCT data were then analyzed using Fiji R (Schindelin et al, 2012).…”
Section: Micro-computed Tomographic (µCt) Studies Of Materials Structuresmentioning
confidence: 99%
“…The beamline addresses a large user community for multi-scale and multi-modal science. User friendliness and ease for data analyses are implemented by the SAVU software pipeline [1] and in particular for ptychography by the PtyREX software [2]. Users may visit after experiments to conduct data analyses (visualisations, segmentations, measurements, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Faster acquisition and a high level of automation is essential to study dynamic phenomena and at the same time enables experiments with significantly increased sample throughput. For example, in 2015 Diamond Light Source (DLS) reported that typically about 3000 scans are recorded during 5 days of operation at a single imaging beamline [7]. Consequently, the amount of data generated at imaging beamlines quickly grows and results in a steep rise of the required computing power.…”
Section: Introductionmentioning
confidence: 99%